Commentary: faculty development: the road less traveled - Steinert, Yvonne (Academic medicine, 2011)
The 2020 Vision of Faculty Development Across the Medical Education Continuum conference, and the resulting articles in this issue, addressed a number of topics related to the future of faculty development. Focusing primarily on the development of faculty members as teachers, conference participants debated issues related to core teaching competencies, barriers to effective teaching, competency-based assessment, relationship-centered care, the hidden curriculum that faculty members encounter, instructional technologies, continuing medical education, and research on faculty development. However, a number of subjects were not addressed. If faculty development is meant to play a leading role in ensuring that academic medicine remains responsive to faculty members and societal needs, additional themes should be considered. Medical educators should broaden the focus of faculty development and target the various roles that clinicians and basic scientists play, including those of leader and scholar. They must also remember that faculty development can play a critical role in curricular and organizational change and thus enlarge the scope of faculty development by moving beyond formal, structured activities, incorporating notions of self-directed learning, peer mentoring, and work-based learning. In addition, medical educators should try to situate faculty development in a more global context and collaborate with international colleagues in the transformation of medical education and health care delivery. It has been said that faculty development can play a critical role in promoting culture change at a number of levels. A broader mandate, innovative programming that takes advantage of communities of practice, and new partnerships can help to achieve this objective.